THE ROLE OF RELIGION TOWARD AMERICAN STRUGGLES - Asih Ernawati (University of Muhammadiyah Purwokerto, 2007)
This essay of African American history is intended to elucidate the role that African Christianity plays in African American struggles in achieveing the American ideals of freedom and equality. Upon the opinion that American people owe much from African American struggles the real meaning of freedom and equality which come from long historical strike for theri lives and liberties in the American land. This essay elaborate African American struggles from antebellum period into civil right movement in 1960s.